Corporate Storytelling as a Strategic Communication Approach to Building Public Awareness: The Case of Grandma Foundation - Dwi Ulina Sari; Mauly Arzak Julika (DEPARTEMENT OF COMMUNICATION AND ISLAMIC BROADCASTING STUDIES, 2026)
Public awareness is essential for the sustainability of non-profit organizations, yet many still rely on informational communication that fails to create meaningful public engagement. This study examines how the Grandma Foundation employs corporate storytelling to enhance public awareness through digital communication. A qualitative case study approach was adopted, with data collected through in-depth interviews, observation, Instagram content analysis, and documentation. The data were analyzed using reflexive thematic analysis. The findings indicate that before implementing storytelling, the Foundation's communication was predominantly descriptive and founder-centered, resulting in limited audience awareness and engagement. The adoption of serialized storytelling, particularly through the Jejak Baik campaign, enabled the organization to communicate authentic humanitarian experiences that strengthened audience attention, emotional connection, and trust. These findings are consistent with the perspectives of emotional branding and Uses and Gratifications theory, suggesting that authentic narratives are more effective than conventional promotional content in building organizational visibility. However, storytelling has not yet fully translated awareness into concrete public participation because explicit call-to-action elements and interactive audience engagement remain limited. This study concludes that corporate storytelling is an effective strategic communication approach for strengthening public awareness in the non-profit sector. The findings imply that storytelling should be integrated with persuasive call-to-action strategies and more dialogic digital engagement to convert audience awareness into sustained participation, volunteer involvement, and donor support. The study also contributes to the literature on strategic communication by demonstrating how authentic storytelling can strengthen the effectiveness of digital communication for non-profit organizations.